RANCANG BANGUN APLIKASI PEMILIHAN RT DAN RW ONLINE BERBASIS ANDROID - Mualimin; Nopriadi, Nopriadi (LPPM Universitas Putera Batam, 2022)
This increasingly rapid technological development has been considered to be able to influence mostj aspectsz of people lives in various fields. Activities that adopt the electoral system carried out by the KPU are preceded by the delivery of the vision and mission of the RT and RW candidates. So far, voting is done by ticking or coblob on the ballot paper as an option in organizing elections. This method is considered still very conventional in the midst of advances in technology and information, has weaknesses in terms of efficiency and effectiveness. By utilizing technology using the android application system, it can make RT and RW election activities easier in conveying information, faster in doing so, the results obtained are more effective and efficient. The purpose of this research is to build an android-based online rt and rw selection system.